2017
DOI: 10.1002/lio2.67
|View full text |Cite
|
Sign up to set email alerts
|

The role of antibiotics in pediatric chronic rhinosinusitis

Abstract: ObjectivesPresenting the role of antibiotics in pediatric chronic rhinosinusitis based on its pathophysiology and microbiology.Data sourceReview of the literature searching PubMed for microbiology and treatment of pediatric chronic rhinosinusitis.ResultsChronic rhinosinusitis (CRS) is an inflammatory condition of the paranasal sinuses that persists for 12 weeks or longer, despite medical management. The microbiology of rhinosinusitis evolves through several stages. The early phase (acute) is generally caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
1
10
0
2
Order By: Relevance
“…The primary antibiotic selection had previously, pre-21st century, shifted to Augmentin (amoxicillin/clavulanate potassium) [1]. Several recent reviews have used extensive search methodologies to summarize clinical studies of CRS in children, and both find the duration of therapy is generally three weeks, although longer is reasonable [1,21]. Alternatives for recalcitrant disease or allergy to penicillin have not been forthcoming, although second and third generation cephalosporins, Clindamycin and Trimethoprim-Sulfamethoxazole have been mentioned [1,21].…”
Section: Pragmatic Perspectivesmentioning
confidence: 99%
“…The primary antibiotic selection had previously, pre-21st century, shifted to Augmentin (amoxicillin/clavulanate potassium) [1]. Several recent reviews have used extensive search methodologies to summarize clinical studies of CRS in children, and both find the duration of therapy is generally three weeks, although longer is reasonable [1,21]. Alternatives for recalcitrant disease or allergy to penicillin have not been forthcoming, although second and third generation cephalosporins, Clindamycin and Trimethoprim-Sulfamethoxazole have been mentioned [1,21].…”
Section: Pragmatic Perspectivesmentioning
confidence: 99%
“…As these studies reflect different epidemiological scenarios, it is difficult to use their data when approaching the choice of antibiotic treatment. However, on the basis of the etiological agents found in CRS, Brook [15] recently suggested an initial, empirical selection of anti-microbial agents effective against the most likely aerobic ( S. pneumoniae , H. influenzae , and M. catarrhalis ) and anaerobic bacterial pathogens, ( Fusobacterium nucleatum , pigmented Prevotella , Porphyromonas , and Peptostreptococcus spp ), especially in the case of community-acquired infections, while also covering methicillin-resistant S. aureus (MRSA).…”
Section: Historical Epidemiology Of Pediatric Crsmentioning
confidence: 99%
“…They did not reach agreement about the appropriate antibiotic treatment including a minimum of 10 consecutive days, but they agreed on the superiority of a 20-day compared to a 10-day treatment regimen of systemic antibiotic treatment and on the fact that culture-directed antibiotic therapy may improve clinical outcomes in patients not responding to empirical treatment for CRS [55]. More recently, a review [56] about the role of antibiotic treatment in paediatric CRS identified three possible alternative oral treatment regimens effective against polymicrobial infections possibly substained by beta-lactamase-producing aerobic and anaerobic pathogens. They included amoxicillin-calvulanate as the first-line option (at the dosage of 45 mg/kg/day divided into two doses; the 90-mg/kg/day dose should be used in children from geographic areas with a high endemic rate of invasive penicillin-nonsusceptible S. pneumoniae and in those with severe infection, attending daycare, younger than 2 years, with immune defects, recent hospitalisation, or antibiotic assumption) or clindamycin (20–40 mg/kg/day divided into a dose every 6–8 h) in penicillin-allergic children.…”
Section: Discussionmentioning
confidence: 99%
“…They included amoxicillin-calvulanate as the first-line option (at the dosage of 45 mg/kg/day divided into two doses; the 90-mg/kg/day dose should be used in children from geographic areas with a high endemic rate of invasive penicillin-nonsusceptible S. pneumoniae and in those with severe infection, attending daycare, younger than 2 years, with immune defects, recent hospitalisation, or antibiotic assumption) or clindamycin (20–40 mg/kg/day divided into a dose every 6–8 h) in penicillin-allergic children. Refractory cases should be treated with metronidazole (30–50 mg/kg/day divided into three daily doses) plus one molecule that is active against aerobic and facultative bacteria (cefuroxime axetil, cefdinir, cefpodoxime proxetil, azithromycin, clarithromycin, trimethoprim-sulfamethoxazole) [56].…”
Section: Discussionmentioning
confidence: 99%